Ecohydrological flow networks in the subsurface. Issue 4 (August 2014) - Band, L. E.; McDonnell, J. J.; Duncan, J. M.; Barros, A.; Bejan, A.; Burt, T.; Dietrich, W. E.; Emanuel, R. E.; Hwang, T.; Katul, G.; Kim, Y.; McGlynn, B.; et al.
ABSTRACT Preferential flow in hillslope systems through subsurface networks developed from a range of botanical, faunal and geophysical processes have been observed and inferred for decades and may provide a large component of the bulk transport of water and solutes. However, our dominant paradigm for understanding and modelling hillslope hydrologic processes is still based on the Darcy–Richards matric flow framework, now with a set of additional methods to attempt to reproduce some of the aggregate function of the two‐phase system of network and matrix flow. We call for a community effort to design and implement a set of well planned experiments in different natural and constructed hillslopes, coupled with the development of new theory and methods to explicitly incorporate and couple the co‐evolution of subsurface flow networks as intrinsic components of hydrological, ecological and geomorphic systems. This is a major community challenge that can now benefit from new experimental infrastructure, renewal of older infrastructure and recent advances in sensor systems and computational capacity but will also require a sustained and organized interdisciplinary approach. Copyright © 2014 John Wiley & Sons, Ltd.